A new hybrid from Taiwan, Elatostema ×hybrida (Urticaceae), is the first confirmed natural hybrid for Urticaceae - Tseng, Yu-Hsin; Hu, Jer-Ming (Phytotaxa, 2014)
Explosive pollen dispersal is common in Urticaceae and they are thought to be wind-pollinated. Despite a lack of obvious mechanism for preventing cross-species pollination, putative hybrid species in Urticaceae are rarely documented. Here we described the first natural hybrid in Urticaceae Elatostema ×hybrida from Taiwan. Morphological characters in E. ×hybrida are intermediate between putative parental species: E. lineolatum var. majus and E. platyphylloides. Six hybrid populations of E. ×hybrida were found in Taiwan that exhibited largely overlapping distribution patterns with its putative parents. Phylogenetic analysis of chloroplast DNA showed that the hybrid species is more closely related to E. lineolatum var. majus suggesting that the latter is the maternal parent and that hybridization is unidirectional. The chromosome number of E. ×hybrida remains the same as its putative parents (2n = 26). We speculate that the examined hybrids are natural first-generation results of independent hybridization events. Based on the morphology, spatial distribution, DNA sequence data, pollen viability and cytological observations, we hypothesize that E. ×hybrida is derived from natural hybridization events between E. lineolatum var. majus (♀) and E. platyphylloides (♂).